The Clinicopathologic and Prognostic Value of Altered Chromosome 17 Centromere Copy Number in HER2 Fish Equivocal Breast Carcinomas - Ji, Hongfei (PLoS One, 2015)
Chromosome 17 centromere (CEP17) gain is frequently observed in breast cancer by fluorescence in situ hybridization (FISH). To address the biologic characteristics and clinical significance of CEP17 gain in a large population of breast cancer patients, we performed FISH on a series of 770 breast cancer tissues to evaluate the status of human epidermal growth factor receptor 2 (HER2) gene and CEP17 by immunohistochemistry (IHC) and FISH. Among the 770 specimens, 184 cases showed CEP17 gain (23.9%). Histological grade, nodal status, HER2 by IHC, Ki 67 index, and p53 expression were significantly different between CEP17 gain tumors and HER2-positive tumors. In contrast with HER2-negative tumors, CEP17 gain tumors showed higher histological grade, higher HER2 score by IHC, and higher Ki 67 index. The patients with CEP17 gain tumors had an intermediate survival between HER2-negative and HER2-positive patients. By comparison to HER2-negative and HER2-positive patients, survival in luminal B patients with CEP17 gain tumors also fell in between. In conclusion, CEP17 gain tumors show specific differences compared with HER2-negative and HER2-positive tumors in clinical parameters and prognosis.